An evaluation of grati bull fertility in Pujon East Java - A. Winanta (Hemera Zoa, 1991)
A total of 258 measurements of scrotal circumference (SC) was made on 53 Grati bulls in Pujon, East Java, from June 1981 unti June 1985. Body weight (BW) and age of bulls ranged from 110 to 393 kg and from 12 to 65 months, respectively. The cummulative BW increased rapidly until about 32 months of age and there after slowly to a maximum of 393 kg at 54 monts age. The curviliear regression to fit BW data was Y = -25.83+14.27x - 0.13X2 where Y=BW in kg and X=age in months (r2=0.91).